2019
DOI: 10.1177/0021998319893435
|View full text |Cite
|
Sign up to set email alerts
|

Low-velocity impact behavior of glass fiber epoxy composites modified with nanoceramic particles

Abstract: The introduction of new type of nanomaterials has provided challenges in a deeper level understanding of mechanical behavior and failure mechanisms of fiber-reinforced composites. In this study, a comparison of low-velocity impact behavior of E-Glass epoxy composites modified with 10 wt% nanosilica and 2.5 wt% Nafen™ alumina nanofibers manufactured using vacuum-assisted resin transfer molding is reported. Low-velocity impact tests at three impact energies of 29 J, 39 J, and 50 J are conducted and impact respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In reality, composite materials are likely to be subjected to unintended shocks from a variety of sources, including aeronautics, tool drops during repair, impacts between two panels during assembly, bird strikes during service life, 13,14 and shocks or stone impacts in vehicles over the course of their lifetime. 15,16 Several research studies have been performed in recent years to further understand the impact behavior of synthetic fiber composites such as carbon, 17 glass, 18 and kevlar 19 in order to create structures that are more tolerant to low-velocity impact damage, which is determined by the material characteristics (matrix and fiber types, reinforcement architecture, stacking sequence, fibermatrix interface quality, and component thickness) as well as the impactor shape. 16,20 Impact damage reduces the residual mechanical strength of these structures, which has a major impact on their service life.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, composite materials are likely to be subjected to unintended shocks from a variety of sources, including aeronautics, tool drops during repair, impacts between two panels during assembly, bird strikes during service life, 13,14 and shocks or stone impacts in vehicles over the course of their lifetime. 15,16 Several research studies have been performed in recent years to further understand the impact behavior of synthetic fiber composites such as carbon, 17 glass, 18 and kevlar 19 in order to create structures that are more tolerant to low-velocity impact damage, which is determined by the material characteristics (matrix and fiber types, reinforcement architecture, stacking sequence, fibermatrix interface quality, and component thickness) as well as the impactor shape. 16,20 Impact damage reduces the residual mechanical strength of these structures, which has a major impact on their service life.…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, an addition of 0.2 wt.% Cloisite 20A led to a significant increase in the maximum impact force (up to 25.7%) and a decrease in the maximum displacement (up to−29.08%). Kallagunta and Tate 9 compared the low-velocity impact behavior of the neat and nano-reinforced composites. The damage areas were evaluated by optical microscopy and infrared thermography.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that nanosilica particles were affecting the tensile, flexural, and energy absorption capacity of the glass/epoxy composites. Kallagunta and Tate [24] modified epoxy resin with 10 wt.% nano-silica to investigate the low-velocity impact behaviour of glass/epoxy composites under different impact energies. They reported that compared to unmodified composites, the nanoparticle modification resulted with high peak forces, also with rising impact forces, the density of failure mechanisms from matrix failure to fiber failure increases.…”
Section: Introductionmentioning
confidence: 99%